Structure of bis(4-Methyl Pyridine) Cadmium Tetracyanonickelate - Erdönmez, Ahmet; Işık, Şamil; Büyükgüngör, Orhan; Nardin, Gingio; AKYÜZ, SEVİM (Taylor and Francis Online, 1998)
The structure, C16H14CdN6Ni, consist of corrugated polymeric networks made up of tetracyanonickelate ions coordinated to Cd. The 4-methyl pyridine molecules bound to Cd in trans positions are located on both sides of the network. The bonding in the networks occurs because of a departure of the Ni-C-N-Cd sequence of atoms from linearity at the C and N positions. The crystal structure of the title compound was determined as monoclinic by single crystal X-Ray diffraction technique. The crystal parameters of this compound are as follows: monoclinic C2/m, a=18.156(2) Å, b=7.581(2) Å. c= 6.983(2) Å, β = 110.09(2)°, V = 902.6(5) Å3 Z=2, Dx = 1.698 g/cm3, F(000) - 456, λ (MoKα) = 0.71070 Å, μ = 2.121 mm−1. The structure was solved by SHELXS-86 and refined by SHELXL-93. R = 0.02 for 1074 observed reflections with I > 2[sgrave] (I).